MENINGKATKAN PENGUASAAN KOSA KATA MENGGUNAKAN METODE TEKA TEKI SILANG PADA ANAK BERKESULITAN BELAJAR - Pitrianti - (Jurnal Penelitian Pendidikan Khusus, 2016)
Pitrianti. 2016. "Improving Vocabulary Mastery Method Using Crosswords Puzzles in Children learning disabilities" Thesis. Department of Special Education, Faculty of Education, State University of Padang.This research was motivated by the problems that the researchers found in SD Negeri 14 Koto Panjang Padang, a child is having trouble learning disabilities such as low capacity of the mastery of vocabulary. This study aims to improve the mastery of vocabulary using a crossword in children learning disabilities in SDNegeri 14 Koto Panjang Padang.This research uses experimental approach in the form of single subject research (SSR) with the design of the A1-B-A2 and analysis of research data using a visual graph analysis techniques. His research interests of a child learning difficulties Elementary third grade, children are asked to write the vocabulary of nouns, verbs and adjectives into the puzzle. Many problems are given 10 pieces about each meeting. Measurement variables by using percentages.The results of this study indicate that the method of the crossword puzzle can enhance vocabulary mastery learning disabilities in children. This is proved by the results of the baseline (A1) which is held six times observation, the percentage of the ability to master the vocabulary of the child remains in the range of 40%. The results of the intervention (B) using the method of the crossword puzzle by clue at the beginning said the observations were made eight meetings, the percentage of the ability to master the vocabulary using a crossword acquisition value varies stable capability at a meeting of 12, 13 and 14 with a score of 60% , Baseline (A2) after no longer given the clue at the beginning of a word in the puzzle to do as much as six times observation, the result is the child's ability in mastering the vocabulary increased and stabilized on the 18, 19 and 20 with a value of 80%. Based on these results we can conclude the crossword puzzle method can improve the ability of mastering vocabulary learning disabilities in children. Researchers suggest the teacher should be able to use the methods of the crossword puzzle to improve the mastery of vocabulary in children learning difficulties. Keywords: Mastery of vocabulary, methods crossword puzzles, children learning disabilities.